Association between bowel movement disorders and depressive symptoms: a cross-sectional study - Wang, Linyue; Tian, Maosheng; Sun, Hongyuan; Gao, Jihua; Qi, Wenyue; Xu, Jiancheng; An, Yongkang; Xu, Wencong (Frontiers in Psychiatry, 2024)
Objectives: This study aimed to explore the association between bowel movement disorders and depression in adults. Method: A cross-sectional study was conducted using data from the National Health and Nutritional Examination Survey (NHANES), 2005–2010. Depression, constipation, diarrhea, and fecal incontinence were self-reported via questionnaires. Weighted logistic regression and subgroup analyses were performed to explore the association between bowel movement disorders and the risk of depression. Restricted cubic spline (RCS) was also conducted to investigate the association between bowel movements disorder and depression. Results: A total of 13,820 participants were collected. Compared to the participants with normal bowel movements, the full-adjusted depression model ORs for constipation and diarrhea were 2.28 (95%CI,1.78-2.92), 1.75 (95%CI,1.31-2.31), respectively. Any kind of bowel leakage were associated with depression. The RCS showed the possible nonlinear association between bowel movement frequency/stool shape and depression. Conclusions: Constipation, diarrhea, and bowel leakage are associated with an increased risk of depression.